THE COURSE "FUNDAMENTALS OF DISTANCE LEARNING IN PRIMARY EDUCATION" AS A COMPONENT OF LIFELONG EDUCATION OF PRIMARY SCHOOL TEACHERS - O. Mukoviz (Kherson State University, 2014)
The modern information society raises new requirements to the process of training of a future primary school teacher as a component of a lifelong education system. An important role in providing of lifelong learning is given to distance education, which promotes self-motivation and self-actualization, enhances independent cognitive activity, and contributes to the acquisition of fundamental knowledge and the formation of skills to use it in professional activity. In this regard, the article analyzes the course "Fundamentals of Distance Learning in Primary Education" that contributes to the training of future primary school teachers to the successful use of distance learning technologies in the system of lifelong education. The course consists of two modules. The first module provides theoretical information on a distance learning technology in primary education, and the other - individual research assignments. Also, the paper presents the topics of lectures, practical classes and independent activity and describes the system of student performance evaluation. In general, the course facilitates the development of systems thinking of future specialists and the learning of theoretical, methodological and practical problems of forming, functioning and development of a lifelong education system.